2020
DOI: 10.1097/cm9.0000000000000881
|View full text |Cite
|
Sign up to set email alerts
|

Trans-cranial Doppler predicts early neurologic deterioration in anterior circulation ischemic stroke after successful endovascular treatment

Abstract: Background Early neurologic deterioration (END) may occur in patients with anterior circulation ischemic stroke (ACIS) after receiving endovascular treatment (EVT). Hemodynamic insufficiency, re-occlusion, and post-re-canalization hyper-perfusion are likely to play a critical role in END. We hypothesized that hemodynamic changes can predict END in patients with ACIS post-successful EVT using trans-cranial Doppler (TCD). Methods We utilized a prospectively maintained dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…First, a previous ROC analysis has suggested that PSV ≥ 118 cm/s was an independent risk factor for early neurological deterioration, with a sensitivity of 88.1% and a specificity of 52.4%, respectively. Moreover, the risk of sICH and vasogenic cerebral edema also increased significantly when PSV ≥ 118 cm/s ( 14 ). Second, iMFV/cMFV ≥ 1.25 was chosen because Kneihsl et al found that the risk of postinterventional ICH (OR 3.6, 95% CI 1.1 to 13.2) and mRS 3–6 at 90 days (OR 3.2, CI 1.1–9.7) increased significantly when MFV on the lesion side was higher than 125% that on the opposite side ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a previous ROC analysis has suggested that PSV ≥ 118 cm/s was an independent risk factor for early neurological deterioration, with a sensitivity of 88.1% and a specificity of 52.4%, respectively. Moreover, the risk of sICH and vasogenic cerebral edema also increased significantly when PSV ≥ 118 cm/s ( 14 ). Second, iMFV/cMFV ≥ 1.25 was chosen because Kneihsl et al found that the risk of postinterventional ICH (OR 3.6, 95% CI 1.1 to 13.2) and mRS 3–6 at 90 days (OR 3.2, CI 1.1–9.7) increased significantly when MFV on the lesion side was higher than 125% that on the opposite side ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mean flow velocity (MFV) was calculated automatically using the following equation: MFV = (PSV – EDV) / 3 + EDV. PSV was selected as the primary target in this study because previous research showed that the risk of early neurological deterioration significantly increased when PSV ≤74 cm/s or ≥118 cm/s among patients after anterior circulation EVT ( 14 ). A continuous monitoring of MCA cerebral blood flow velocity was conducted, and an automatic reminder was set up when PSV ≥ 118 cm/s, MFV on the lesion side was higher than 125% that on the opposite side, and PSV ≤ 74 cm/s ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, TCDNM can identify the sudden appearance of echogenic material (ie, emboli) 51,52,54–57 . In certain clinical situations, each of these pieces of information, unobtainable by other means, may be literally lifesaving 58–60 …”
Section: Tcd Monitoring Rationalementioning
confidence: 99%
“…Ischemic stroke accounts for 69.6–70.8% of all strokes (Wang W. et al, 2017 ). The mortality rate of patients with acute ischemic stroke is as high as 2.3–3.2% within 1 month after onset (Huang et al, 2010 ; Wang D. et al, 2017 ; Li et al, 2019 ; He et al, 2020 ). The formation of cerebral edema is a major cause of death in stroke patients (Simard et al, 2007 ; Walcott et al, 2014 ; Rungta et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%